2022
DOI: 10.1177/03000605221117134
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic retinopathy in the Eastern Mediterranean Region: a systematic review and meta-analysis

Abstract: Objectives Individual studies in the Eastern Mediterranean Region (EMR) have shown the high prevalence of diabetic retinopathy. We conducted a meta-analysis to yield an estimate of the prevalence of diabetic (type 1 and 2) retinopathy in the EMR. Additionally, we explored its potential modulators. Methods Two-step screening of relevant articles published from 1 January 2000 to 13 December 2019 was carried out. An estimation of summary proportions, subgroup analysis, meta-regression, and publication bias assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 135 publications
0
1
0
Order By: Relevance
“…The study rates in our research exhibit a lesser magnitude in comparison to those observed in Jordan, although they demonstrate a greater level when compared to other economically developed Arabic nations such as Kuwait and Bahrain [34]. In a similar manner, our observed prevalence exhibited a lesser magnitude when compared to Australia, Colombia, and Iran although it displayed a larger magnitude in relation to the studies conducted in Ireland [35].…”
Section: Prevalence Rates Of Diabetes-related Complicationssupporting
confidence: 49%
See 1 more Smart Citation
“…The study rates in our research exhibit a lesser magnitude in comparison to those observed in Jordan, although they demonstrate a greater level when compared to other economically developed Arabic nations such as Kuwait and Bahrain [34]. In a similar manner, our observed prevalence exhibited a lesser magnitude when compared to Australia, Colombia, and Iran although it displayed a larger magnitude in relation to the studies conducted in Ireland [35].…”
Section: Prevalence Rates Of Diabetes-related Complicationssupporting
confidence: 49%
“…The prevalence of retinopathy exhibited variation among different countries within the region, with Egypt reporting a rate of 41.5%, the Gulf countries observing a rate of 29.9%, and Tunisia documenting a rate of 8.1% [37,38]. According to a systematic review conducted on the incidence of diabetic retinopathy in the Eastern Mediterranean Region, the estimated prevalence of this condition was found to be 31% [35]. Multiple factors, such as population characteristics, sample size, and the diagnostic process employed, could potentially contribute to the observed variations.…”
Section: Prevalence Rates Of Diabetes-related Complicationsmentioning
confidence: 99%
“…[16,39] Various risk factors are linked to retinopathy in individuals with diabetes, with age, duration of diabetes, high body mass index, hyperglycemia, high blood pressure and hypercholesterolemia being the most significant factors. [40] According to some articles, there is a potential connection between diabetic retinopathy and inflammation, as well as the dysregulation of various inflammatory mediators. [17] Wei-Jing Zhao et al, examined how vitamin D levels affect microvascular complications (diabetic retinopathy, diabetic nephropathy, diabetic peripheral neuropathy) in individuals with type 2 diabetes mellitus.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…We consulted previous systemic reviews to examine DR prevalence in patients with type 2 diabetes in a general cohort [78][79][80][81][82][83] (Table 11). The global DR prevalence was 22.2-34.6% [78][79][80], but those of China and India were lower [81,82].…”
Section: Pathophysiology Of Dmementioning
confidence: 99%